The Effect of Clinical Pilates on Functional Movement in Recreational Runners - Laws, Anna; Williams, Sean; Wilson, Cassie (International Journal of Sports Medicine, 2017)
Biomechanical imbalances and inefficient functional movements are considered contributing factors to running-related injuries. Clinical Pilates uses a series of exercises focused on retraining normal movement patterns. This study investigated whether a 6-week course of Clinical Pilates improves functional movement and thereby, potentially, reduces the risk of running-related injuries associated with movement dysfunction. A modified functional movement screen was used to analyze the functional movement ability of forty runners. Forty participants completed a 6-week course of Clinical Pilates delivered by a Clinical Pilates instructor. The movement screen was carried out 3 times for each runner: 6 weeks pre-intervention (baseline), within one week pre-intervention (pre) and within one week post-intervention (post). Repeated-measures analysis of variance and post-hoc tests found significant increases in scores between baseline and post (mean±SD; 13.4±2.4 vs. 17.0±1.7, p<0.01) and pre and post (mean±SD; 13.5±2.5 vs. 17.0±1.7, p<0.01), but no significant difference between baseline and pre (p=0.3). A 6-week course of Clinical Pilates significantly improves functional movement in recreational runners, and this may lead to a reduction in the risk of running-related injuries.
Keywords: pilates; functional; movement; injury; running